Exogenous naphthaleneacetic acid alleviated alkalinity-induced morpho-physio-biochemical damages in Cyperus esculentus L. var. sativus Boeck - Ullah, Abd; Zeng, Fanjiang; Tariq, Akash; Asghar, Muhammad Ahsan; Saleem, Khansa; Raza, Ali; Naseer, Muhammad Asad; Zhang, Zhihao; Noor, Javaria (Frontiers in Plant Science, 2022)
Cyperus esculentus L. var. sativus Boeck (commonly called Chufa) is a perennial species that produces nutritious underground tubers and contributes to the diet and health of human worldwide. However, it is salt-sensitive and its adaptation to salinity stress remains an enigma. Naphthaleneacetic acid (NAA) plays a vital role in regulating plant salt stress tolerance. Thus, we aimed to investigate the impact of NAA (150 mg/L) application on growth and physio-biochemical response mechanisms of Chufa plants to different levels of salinity stress (0-, 90-, and 180 mM of alkaline stress ([1:1 ratio of Na2CO3 and NaHCO3]). In response to increasing stress levels, shoot-root growth decreased, whereas malondialdehyde (MDA), hydrogen peroxide (H2O2), osmolytes (soluble protein, proline, and soluble sugars), and activities of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT) significantly increased. Alkalinity led to significant increase in Na+ and Cl–, but decrease in Mg2+ concentration in both roots and leaves; however, K+ decreased significantly in leaves under both stresses. Additionally, NO3- and NH4+ levels, nitrate reductase (NR) activities, and glutamate synthase (GOGAT) decreased significantly. However, glutamine synthetase (GS) increased non-significantly at 90 mM but declined at 180 mM. Foliar NAA application reduced Na+ and Cl-, MDA, and H2O2 but increased photosynthetic pigments, K+ and Mg2+, osmolytes, nitrogen (N) metabolism, and upregulating the enzymatic antioxidant system to reduce oxidative stress under alkaline conditions. Hence, our findings manifest that NAA application is an effective strategy that can be utilized to enhance tolerance of chufa plants to alkaline stress. Future studies should explore whether NAA can positively alter the nutrient composition of chufa tubers at deeper molecular levels, which might offer solutions to nutritious problems in developing countries.